RELEVANSI KURIKULUM MERDEKA DALAM PERSPEKTIF FILSAFAT EKSISTENSIALISME DI ABAD 21 - Musfirah Firah; Ismail (Jurnal Genta Mulia, 2024)
The Merdeka Curriculum is a curriculum designed by the Ministry of Education and Culture to overcome the learning crisis and 21st Century Education in Indonesia. The essence of the independent curriculum is independent learning, which is a concept created so that students can explore their respective interests and talents. The independent curriculum will begin to be implemented in Indonesia in 2022. This curriculum is still relatively new so it needs to be studied from various perspectives regarding the implementation of independent learning. This research uses a qualitative research method based on library research. The results of this research reveal that the independent curriculum currently being implemented in Indonesia is relevant to the perspective of existentialism philosophy. In essence, educators are no longer the only source of knowledge, educators are more emphasized as facilitators to accompany students to discover and develop their potential as optimally as possible. In this way, it is hoped that an atmosphere of mutual support in learning will be created, creating happiness and a sense of comfort in learning so that in the future educational goals can be realized and the quality of education in Indonesia continues to improve.